Reflections of a disk-less Inuk on Canada’s Eskimo identification system - Dunning, Norma (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2012)
This essay examines the reactions of several Inuit women to an identification system whereby from 1941 to 1978 the Canadian government required the Inuit to wear small numbered disks. The author presents each Inuk woman’s personal perspectives, including her own, through narratives, interviews, and songs. The second part discusses the historical context of the “Eskimo disk list” system and its repercussions decades after it was discontinued.